2023
DOI: 10.1158/1078-0432.c.6522914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Trop-2 Induces Tumor Growth Through AKT and Determines Sensitivity to AKT Inhibitors

Abstract: <div>Abstract<p><b>Purpose:</b> Inhibition of AKT is a key target area for personalized cancer medicine. However, predictive markers of response to AKT inhibitors are lacking. Correspondingly, the AKT-dependent chain of command for tumor growth, which will mediate AKT-dependent therapeutic responses, remains unclear.</p><p><b>Experimental Design:</b> Proteomic profiling was utilized to identify nodal hubs of the Trop-2 cancer growth–driving network. Kinase-specif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A resent study confirmed that enhanced invasion and metastasis of colorectal cancer cells is the result of MMP-2 activation of the FAK Tyr397 /ERK pathway via the CD9-α7β1 integrin complex (Kwon et al, 2021). Also, Santos MF et al (Guerra et al, 2022) have found that CD9 interacts with Trop-2 and enhances the growth of colorectal cancer cells through remodeling of β-actin cytoskeleton, proteolytic cleavage of E-cadherin, and activation of Raf-MEK-ERK and PI3K-PDK1-Akt pathways. Inhibition of CD9 expression in pancreatic ductal adenocarcinoma inhibited the uptake of annexin A6 extracellular vesicles into cancer cells and impaired annexin A6-induced cell migration and EMT processes via the p38 MAPK pathway (Nigri et al, 2022).…”
Section: Cd9mentioning
confidence: 83%
“…A resent study confirmed that enhanced invasion and metastasis of colorectal cancer cells is the result of MMP-2 activation of the FAK Tyr397 /ERK pathway via the CD9-α7β1 integrin complex (Kwon et al, 2021). Also, Santos MF et al (Guerra et al, 2022) have found that CD9 interacts with Trop-2 and enhances the growth of colorectal cancer cells through remodeling of β-actin cytoskeleton, proteolytic cleavage of E-cadherin, and activation of Raf-MEK-ERK and PI3K-PDK1-Akt pathways. Inhibition of CD9 expression in pancreatic ductal adenocarcinoma inhibited the uptake of annexin A6 extracellular vesicles into cancer cells and impaired annexin A6-induced cell migration and EMT processes via the p38 MAPK pathway (Nigri et al, 2022).…”
Section: Cd9mentioning
confidence: 83%